Evaluating the percentage of handicapped individuals using media in Herat province - Sarwary, Namatullah (International Journal of Innovative Research and Scientific Studies, 2020)
Afghanistan is among the countries where majority of its people deal with tough circumstances. People with disabilities have more critical condition than others; they are deprived from many facilities and equipment, especially access to media. This research investigates the extent handicapped people use media and the impact of media on these people. By employing a qualitative method, data were collected from 21 disabled people through in-depth semistructured interviews. The results demonstrated that a large number of handicapped individuals use media. The media which had been used among the handicapped individuals were radio, television, and magazines, whereas Radio was considered more practical. Media can have either positive or negative impacts on disabled people, but this impact differs among disabled people depending on their disabilities.